The age of the giant Golden Mile Deposit, Kalgoorlie, Western Australia: ion-microprobe zircon and monazite U-Pb geochronology of a synmineralization lamprophyre dike. - McNaughton, Neal; Mueller, A.; Groves, D. (Society of Economic Geologists Inc, 2005)
Open-pit and underground mines in the Golden Mile at Kalgoorlie, Western Australia, have produced more than 1,475 metric tons (t) of gold since 1893. Despite the economic importance of the deposit, the age of the mineralized shear zone array and its temporal relationship to other structures and to porphyry intrusions in the host greenstone terrane are poorly constrained. In this study, the SHRIMP ion microprobe has been used to date zircons and monazites recovered from a chlorite-carbonate–altered, synmineralization lamprophyre dike intruded into sericite-ankerite–altered Paringa basalt below the high-grade Oroya hanging-wall shear zone. Analyses of magmatic-hydrothermal zircons define a weighted mean 207Pb/206Pb age of 2642 ± 6 Ma (n = 37, MSWD = 0.88). Analyses of cogenetic hydrothermal monazites yield a concordant 207Pb/206Pb age of 2637 ± 20 Ma (n = 9, MSWD = 1.8).The two alteration and/or mineralization ages, determined independently in two different minerals, are inconsistent with recent structural models relating mineralization to the early compressional events of the D1 to D4 deformation sequence for the terrane. Instead, they confirm earlier structural models relating mineralization to the postfolding wrench tectonic regime which generated regional sinistral faults (D3) coeval with mantle- derived lamprophyric and initial felsic magmatism in the middle to lower Archean crust.